Problems and solutions of ventilation in commercial kitchens - Charkowska, Anna (Instal, 2021)
Ventilation and air conditioning of commercial kitchens, due to the requirements for the safety and comfort of staff work, the variety of catering facilities with different hygienic requirements and thermal and humidity conditions, is an issue that can only recently be solved using current legal acts describing the most modern calculation methods and devices. The subsequent parts of the PN-EN 16282 standard, introduced from 2016 to 2020, allow for the use in design practice of the recommended general supply and exhaust ventilation solutions and air exhaust ventilation through kitchen hoods or exhaust ventilation ceilings. The article, after recalling the withdrawn national Regulations that referred to this issue and the Regulation (EC) of the European Parliament and of the Council of 2004, presents the calculation methods of ventilation air (preliminary and accurate) and describes the recommendations for ventilation devices used in commercial kitchens.